Exploring uptake of HIV/STI knowledge and safer sex-efficacy in an arts-based sexual health workshop among Northern and Indigenous adolescents in the Northwest Territories, Canada. Issue 3 (4th March 2023) - Lys, Candice; Logie, Carmen H.; Mackay, Kayley Inuksuk; MacNeill, Nancy; Loppie, Charlotte; Gittings, Lesley; Yasseen, Abdool
ABSTRACT : Limited research has evaluated sexual health promotion projects with adolescents living in Arctic regions. The study objective was to examine changes in STI knowledge and safer sex efficacy among youth in the Northwest Territories (NWT), Canada who participated in arts-based sexual health workshops. We used a pre/post-test design with a convenience sample of students aged 13–18 years recruited from 17 NWT communities. We conducted summary statistics and comparisons between pre and post-test scores using paired t-tests. Among participants ( n  = 610), we found statistically significant increases in STI knowledge overall (mean difference = 3.9; p  < 0.001) and across gender and age stratifications. There were statistically significant increases in safer sex efficacy overall (mean difference = 0.9, p  < 0.001), across genders, and among participants: aged <15 years, in rural communities, reporting food insecurity, reporting dating violence, and Indigenous youth. No statistically significant differences in safer sex efficacy were observed among participants who were aged ≥15, sexually active, reporting consistent condom use, and using drugs/alcohol. Findings signal the promise of youth-targeted, arts-based sexual health workshops for improving STI knowledge and safer sex efficacy among adolescents in the NWT. Further research can explore how safer sex efficacy may be shaped by age, substance use, and sexual experience to inform tailored interventions.